2005
DOI: 10.4049/jimmunol.174.11.7393
|View full text |Cite
|
Sign up to set email alerts
|

Cross Talk between MyD88 and Focal Adhesion Kinase Pathways

Abstract: Focal adhesion kinase (FAK) is a nonreceptor protein tyrosine kinase involved in signaling downstream of integrins, linking bacterial detection, cell entry, and initiation of proinflammatory response through MAPKs and NF-κB activation. In this study, using protein I/II from Streptococcus mutans as a model activator of FAK, we investigated the potential link between FAK and TLR pathways. Using macrophages from TLR- or MyD88-deficient mice, we report that MyD88 plays a major role in FAK-dependent protein I/II-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 24 publications
4
51
2
Order By: Relevance
“…These findings raise the intriguing possibility that the interaction between TLR4 and FAK may also regulate these cellular process and thereby serve as an important branch point in the signaling events that lead to the development of NEC. In support of this possibility, Zeisel et al (77) have reported a functional interaction between FAK and MyD88 pathways. The current findings provide additional in vivo relevance to these observations.…”
Section: Discussionmentioning
confidence: 75%
“…These findings raise the intriguing possibility that the interaction between TLR4 and FAK may also regulate these cellular process and thereby serve as an important branch point in the signaling events that lead to the development of NEC. In support of this possibility, Zeisel et al (77) have reported a functional interaction between FAK and MyD88 pathways. The current findings provide additional in vivo relevance to these observations.…”
Section: Discussionmentioning
confidence: 75%
“…Previous studies showed that IL-6 and IL-8 release by protein I/II-activated FLS requires crosstalk between myeloid differentiation factor 88 and focal adhesion kinase, which contributes to the TLR and integrin signaling pathways, respectively (19). It is, however, conceivable that protein I/II signaling involved in BAFF synthesis might use distinct downstream signaling molecules belonging to the ␣5␤1 integrin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of PRRs, such as Toll-like receptor 2 (TLR-2), TLR-4, and TLR-9, as well as numerous integrins are expressed by FLS, and their expression is increased in response to inflammatory stimuli (16,17). We previously showed that LPS, bacterial lipopeptide (BLP), and protein I/II, which are ligands of TLR-4, TLR-2, and ␣5␤1 integrin, respectively, can trigger the release of IL-6 and IL-8 from activated FLS (18,19).…”
mentioning
confidence: 99%
“…Indeed, impairment of IL-1R or IL-1 plus IL-18 cleavage by ICE does not prevent bronchoconstriction or neutrophil recruitment in the airways. However, we cannot exclude that other MyD88-dependent pathways such as the recently described involvement of MyD88 in cross-talk with the focal adhesion kinase (45) or other members of the IL-1R family may be involved (46).…”
Section: Discussionmentioning
confidence: 99%